A STUDY ON INTERACTION OF Cd(II) AND DIATOMACEOUS EARTH IN ADSORPTION PROCESS - Nuryono Nuryono; Suyanta Suyanta (Universitas Gadjah Mada, 2004)
In this research, interaction occurring in adsorption process between Cd(II) and active site of diatomaceous earth has been studied. The study was carried out by evaluating Cd(II) adsorption on diatomaceous earth at various pHs, either for the earths without treatment, those after being heated or those treated with sulfuric acid and hydrogen chloride. Adsorption was performed by mixing diatomaceous earth, without and with treatments, and Cd(II) solution for one hour at various pHs (2 - 7), and un-adsorbed metallic ion was analyzed by atomic absorption spectroscopy (AAS). The treatments of diatomaceous earth included heating at temperatures of 300, 500, and 900oC for four hours, treatments with acids (3, 8, and 12 M of H2SO4, and 3, 15, and 18 M of HCl solutions for two hours at 150-200oC). Results showed that the increasing of pH from 2.0 to 3.0 and from 6.0 to 7.0 inclined adsorption of Cd(II) from 13.2 to 23.3 mg/g and from 24.0 to 26.4 mg/g, respectively. At a pH range of 3.0 - 6.0 the adsorption slightly increase from 23.3 to 24.0 mg/g. Heating of diatomaceous earth higher than 500oC caused the adsorption capability to be independence of the pH of solution. On the other hand, treatments with acids (H2SO4 and HCl) caused adsorption capability increased significantly with the increase in pH from 3.0 to 6.0. Adsorption evaluation at the pH range investigated showed that adsorption of Cd(II) on diatomaceous earth may be through interaction between Cd2+ and functional groups of T-OH (T = Si/Al).